2018
DOI: 10.1038/s41598-018-19334-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between brachial-ankle and heart-femoral pulse wave velocities and the rapid decline of kidney function

Abstract: The impact of brachial-ankle pulse wave velocity (baPWV) and heart-femoral pulse wave velocity (hfPWV) on rapid decline of estimated glomerular filtration rate (eGFR) has been inconclusive. The database of a multicenter prospective study of 2238 patients in Korea enrolled from 2011 to 2016 was reviewed. After excluding patients with missing baPWV (n = 257) and eGFR change (n = 180), the study included 1801 non-dialysis chronic kidney disease (CKD) patients. The eGFR change <−5ml/min/1.73 m2/year was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Besides the study by Choo et al, [6] seven other studies have reported on hfPWV and cardiovascular-related outcomes, [7][8][9][10][11][12][13] of which three also included cfPWV. [10][11][12] Collectively, these studies report that hfPWV is positively associated with age, [7] N-terminal pro b-type natriuretic peptide (NT-proBNP),[12] blood pressure, [7] diabetes, [7] albumin-creatinine ratio (ACR) [10] and aldosterone, [9] and negatively associated with either estimated glomerular filtration rate (eGFR).…”
Section: Comparison To Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Besides the study by Choo et al, [6] seven other studies have reported on hfPWV and cardiovascular-related outcomes, [7][8][9][10][11][12][13] of which three also included cfPWV. [10][11][12] Collectively, these studies report that hfPWV is positively associated with age, [7] N-terminal pro b-type natriuretic peptide (NT-proBNP),[12] blood pressure, [7] diabetes, [7] albumin-creatinine ratio (ACR) [10] and aldosterone, [9] and negatively associated with either estimated glomerular filtration rate (eGFR).…”
Section: Comparison To Literaturementioning
confidence: 99%
“…[10][11][12] Collectively, these studies report that hfPWV is positively associated with age, [7] N-terminal pro b-type natriuretic peptide (NT-proBNP),[12] blood pressure, [7] diabetes, [7] albumin-creatinine ratio (ACR) [10] and aldosterone, [9] and negatively associated with either estimated glomerular filtration rate (eGFR). [8,10,12] The comparative studies report that both cfPWV and hfPWV are positively associated with proBNP[12] and ACR, [10] and negatively associated with eGFR, [10] but that the highest quartile of cfPWV was most strongly associated with CVD, especially heart failure. [11] It should be acknowledged that the later study [11] and the current study utilized ARIC participants, and we do report greater variability between hfPWV and cfPWV at higher PWV values.…”
Section: Comparison To Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A VP-1000 analyzer (Collin Co., Komaki, Japan) was used for measuring baPWV. As reported previously,15 this device takes a measurement of ankle-to-brachial index by using the electrocardiogram, phonocardiogram, and pressure waveforms. Pressure waveforms of the brachial and tibial arteries were documented with plethysmographic and oscillometric pressure sensors using occlusion/sensing cuffs that were twined around both arms and both ankles.…”
Section: Methodsmentioning
confidence: 99%
“…The hfPWV approach confers a number of potential advantages over cfPWV: (i) it is simpler to conduct, as the measurement is not dependent on assessment of the carotid artery; (ii) the measurement path is consistent with the blood flow path; and, (iii) it incorporates the proximal aorta. Although measures of hfPWV have previously been used as a clinical or epidemiological cardiovascular monitoring tool (17)(18)(19)(20)(21)(22), only two studies have determined its association with the criterion, cfPWV (13,23). Both studies reported strong correlations (r = 0.81-0.83) between hfPWV and cfPWV in community dwelling healthy middle-aged (13) and older adults (23).…”
Section: Introductionmentioning
confidence: 99%